PENGARUH KARAKTERISTIK PERUSAHAAN DAN GOOD CORPORATE GOVERNANCE TERHADAP RETURN SAHAM - Harianto, Tri Sapta Nugroho Slamet; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research has been conducted in all companies which are listed in the Jakarta Islamic Index (JII) in2011-2015 periods. The purposes of this research is to find out the influence of firm size, profitability,leverage, managerial ownership, institutional ownership, independent commissioner, and auditcommittee to the stock return in annual report of the companies which are incorporated in JakartaIslamic Index (JII). The data collection has been carried out by using content analysis to the annualreport of the company and the summary of company performance through official website of IndonesiaStock Exchange (IDX). The result of the research shows that firm size does not have any influence tothe stock return of the company, profitability has positive influence to the stock price of the company,leverage has negative influence to the stock return of the company, managerial ownership does nothave any influence to the stock return of the company, institutional ownership does not have anyinfluence to the stock return of the company, independent commissioner does not have any influence tothe stock return of the company and audit committee has positive to the stock return of company.Keywords: Stock return, Characteristic of Company, Good Corporate Governance.